Perbandingan Tingkat Pemahaman Asmaâul Husna antara Metode Hanifida dengan Metode Konvensional bagi Siswa SMA - Julinah, Julinah (SYAMIL, 2014)
The aims of the study are: 1) Determining the level of understanding of the Divine Name for students taught using methods hanifida. 2) Determining the level of understanding of the Divine Name for students taught using conventional methods. 3) Knowing a significant difference in the level of understanding of the Divine Name for the students taught with hanifida method and the students taught by conventional method. This research is a quantitative research design that uses one-group comparative pretest posttest design. The research approach used in this study is a comparative approach by comparing the 2 methods used as an experiment. The population in this study were all students of SMA Negeri 3 Samarinda counted 1010. The taking sampling technique used is purposive sampling, i.e. taking class X IPA 1 IPA 2, both classes were sampled by reason of that class have been using hanifida method and conventional method in learning process about the Divine Name in the subject matter of Islamic Religion. Data collection technique used is observation and objective tests. Techniques used in data prerequisite test analysis is normality test, homogeneity test, chi square and hypothesis testing. The results of this study is that the level of understanding of the Divine Name by students taught by using hanifida is very effective. This is proofed by the findings that the average score of conventional method is lower than using hanifida method.Â  The score is 72.13% for and 81.57%.